Evaluation of patients with Parkinson' s disease in terms of psychiatric diseases and related clinical features (Annals of Medical Research, 2022)
Aim: In this article, we aimed to evaluate patients with Parkinson’ s disease (PD) in terms of psychiatric diseases and related clinical features.Materials and Methods: 101 patients diagnosed with PD and 101 randomly selected control cases who applied to general internal medicine and endocrine outpatient clinics were included in the study. All subjects were administered a questionnaire including questions about their sociodemographic and clinical features, and were evaluated by the psychiatrist.Results: The rate of psychiatric disease (42.6%) in the PD group was significantly higher than the control group. Anxiety disorders and depression were the most common among these diseases. Also the use of antidepressant in the PD group was higher than the control group.Conclusion: Psychiatric disorders are seen more frequently in patients with PD than in patients with other physical diseases. Considering that quality of life in patients with PD is associated with psychiatric well-being, psychiatric symptoms in patients are of high clinical importance. The physician’ s awareness of psychiatric symptoms and taking necessary precautions will contribute positively to the treatment of the disease.
Keywords: Parkinson’ s disease; Anxiety; Depression; Dopamine; Serotonin